2016
DOI: 10.3382/ps/pew186
|View full text |Cite
|
Sign up to set email alerts
|

The immunomodulatory effect of vitamin D in chickens is dose-dependent and influenced by calcium and phosphorus levels

Abstract: Vitamin D requirement is estimated to be higher than recommended values for the first two weeks of a broiler chicken's life, and is heavily dependent on the concentrations of Ca and P in the diet. There are data indicating the beneficial effect of higher vitamin D levels on performance and overall health of the chickens. However, data on the role of higher vitamin D levels on the innate immune response of chickens are limited. Therefore, in the current study, we examined the effect of higher doses of vitamin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 35 publications
0
34
1
Order By: Relevance
“…However, the immunomodulatory, anti-inflammatory and anti-coccidia roles of VD 3 or its metabolites have also been demonstrated in chickens [ 21 24 ] and chicken cells [ 23 , 25 ]. In addition, Rodriguez-Lecompte et al [ 26 ] reported that vitamin D or 25(OH)D, both have a robust immunomodulatory property with a more favorable helper T cell (Th2) response in broiler chickens. Aslam et al (1998) [ 27 ] observed that vitamin D deficiency depresses the cellular immune responses in young broiler chicks.…”
Section: Introductionmentioning
confidence: 99%
“…However, the immunomodulatory, anti-inflammatory and anti-coccidia roles of VD 3 or its metabolites have also been demonstrated in chickens [ 21 24 ] and chicken cells [ 23 , 25 ]. In addition, Rodriguez-Lecompte et al [ 26 ] reported that vitamin D or 25(OH)D, both have a robust immunomodulatory property with a more favorable helper T cell (Th2) response in broiler chickens. Aslam et al (1998) [ 27 ] observed that vitamin D deficiency depresses the cellular immune responses in young broiler chicks.…”
Section: Introductionmentioning
confidence: 99%
“…In poultry, 20 and 200 ng/mL (equivalent to 48 and 480 nmol/L) vitamin D 3 has been shown to induce AvBD3, AvBD6, and AvBD9 in chicken embryonic intestinal epithelial cells, while AvBD1, AvBD6, and AvBD9 were induced in a dose-dependent manner in primary monocytes ( Zhang et al., 2016 ). Consistently, CATH-1 and CATH-B1 were dose-dependently induced by dietary vitamin D in the spleen of chickens and that induction was further enhanced by low calcium and phosphorus in the diet, although CATH-3 was suppressed ( Rodriguez-Lecompte et al., 2016 ). However, only CATH-1 was significantly induced in response to 9,800 IU/kg of vitamin D 3 supplementation in the bursa of Fabricius, while no cathelicidins were enhanced by any of the treatments in peripheral blood mononuclear cells ( Rodriguez-Lecompte et al., 2016 ).…”
Section: Impact Of Vitamin D On Hdp Expressionmentioning
confidence: 89%
“…Consistently, CATH-1 and CATH-B1 were dose-dependently induced by dietary vitamin D in the spleen of chickens and that induction was further enhanced by low calcium and phosphorus in the diet, although CATH-3 was suppressed ( Rodriguez-Lecompte et al., 2016 ). However, only CATH-1 was significantly induced in response to 9,800 IU/kg of vitamin D 3 supplementation in the bursa of Fabricius, while no cathelicidins were enhanced by any of the treatments in peripheral blood mononuclear cells ( Rodriguez-Lecompte et al., 2016 ). Intraperitoneal injection of chickens with 5,000 IU/kg of body weight of vitamin D failed to upregulate HDP expression in the chicken intestinal tract, but multiple HDP were synergistically induced in response to both vitamin D and LPS ( Lu et al., 2015 ).…”
Section: Impact Of Vitamin D On Hdp Expressionmentioning
confidence: 89%
“…However, CATH-B1 gene expression seems not restricted to the bursa of Fabricius. Although at much lower levels than found in the bursa, CATH-B1 mRNA was present in several tissues, including spleen and multiple segments of the respiratory and gastrointestinal tract of chicken (Achanta et al, 2012;Rodriguez-Lecompte et al, 2016). CATH-B1 gene expression was also observed in chicken HD11 macrophages and primary monocytes (Sunkara, 2011).…”
Section: Discussionmentioning
confidence: 99%